The Effects of Fishmeal Replacement with Degossypolled Cottonseed Protein on Growth, Serum Biochemistry, Endocrine Responses, Lipid Metabolism, and Antioxidant and Immune Responses in Black Carp (Mylopharyngodon piceus) - Jiao Wei; Yifan Fu; Shinan Feng; Jinjing Zhang; Yuanyuan Zhang; Jiaxing Yu; Pengtian Kang; Chenglong Wu; Haifeng Mi (Animals)
This research investigated the growth, serum biochemistry, antioxidant capability, and immunity impact of black carp fed degossypolled cottonseed protein replacing fishmeal at the levels of 0%, 10%, 20%, 30%, 40%, and 50% (DCP0, DCP10, DCP20, DCP30, DCP40, and DCP50), respectively. The results showed there were no significant changes in growth among these test groups. The activities and mRNA expression levels of amylase and trypsin were heightened in conjunction with 30–40% DCP. Although the insulin contents were reduced with a rise in DCP content, 5-hydroxytryptamino was increased in the DCP40 and DCP50 groups. DCP40 could heighten the levels of low-density lipoprotein cholesterol, triglycerides, total cholesterol, and urea nitrogen. Although lower levels of DCP (≤20%) could increase the total antioxidant capacity compared with the DCP50 group, DCP50 could markedly heighten levels of catalase, glutathione S-transferase, H2O2, and malondialdehyde. Meanwhile, the mRNA levels of Mn-superoxide dismutase, glutathione reductase, glutathione peroxidase, glutamate–cysteine ligase regulatory subunit, and nuclear factor E2-related factor 2 were heightened in the DCP30 group compared with the DCP50 group. The levels of alkaline phosphatase, immunoglobulin M, and liver-expressed antimicrobial peptide 2 were markedly heightened in the liver of the DCP20 group compared with the DCP50 group. In conclusion, a suitable level of DCP (20%) could improve serum biochemical indices and hormone variation, enhance antioxidant capability, and increase immunity in black carp.